2019
DOI: 10.1111/cogs.12776
|View full text |Cite
|
Sign up to set email alerts
|

Gricean Expectations in Online Sentence Comprehension: An ERP Study on the Processing of Scalar Inferences

Abstract: There is substantial support for the general idea that a formalization of comprehenders' expectations about the likely next word in a sentence helps explaining data related to online sentence processing. While much research has focused on syntactic, semantic, and discourse expectations, the present event‐related potentials (ERPs) study investigates neurolinguistic correlates of pragmatic expectations, which arise when comprehenders expect a sentence to conform to Gricean Maxims of Conversation. For predicting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…Importantly for the present considerations, in Augurzky et al (2020), positive and negative quantifiers elicited differential mid-sentence brain responses following the identical pictures, therefore ruling out a strategy according to which participants just focused on the pictorial information and mapped this information with the lexical contents of the color adjective (see also Augurzky et al, 2019, for a study on the scalar quantifier some, which indicates immediate quantifier effects on mid-sentence ERPs).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Importantly for the present considerations, in Augurzky et al (2020), positive and negative quantifiers elicited differential mid-sentence brain responses following the identical pictures, therefore ruling out a strategy according to which participants just focused on the pictorial information and mapped this information with the lexical contents of the color adjective (see also Augurzky et al, 2019, for a study on the scalar quantifier some, which indicates immediate quantifier effects on mid-sentence ERPs).…”
Section: Discussionmentioning
confidence: 72%
“…However, we believe that a unified account for the N400 effects across sentence positions, and also across experiments, may explain the whole range of data more parsimoniously than an account that assumes qualitatively different processes just for the infinitive position in the current experiment. Given the highly comparable ERP effects at early and later positions across studies on quantifier restriction, we consider it unlikely that ERPs at the infinitive and the PP noun in the present study need to be associated with different processes (see the comparable pattern at early and late sentence positions in Augurzky et al, 2016Augurzky et al, , 2019Augurzky et al, , 2020, which examine nominal quantifiers that differ about their semantic properties and pictures that differ concerning their complexity).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Degen and Tanenhaus (2015) showed that implicatures were processed more costly if other scalar terms such as number words were available in the context. Finally, Augurzky et al (2019) observed that the contrast between all vs. some may prime the scalar implicature, more specifically, if such a contrast was not present in the context, the implicature was processed more shallowly.…”
Section: Differences Between the Current And The Prior Erp Study On Scalar Implicaturesmentioning
confidence: 96%